Assessing the stigma content of urinary incontinence intervention outcome measures. (October 2017) - Southall, Kenneth; Tuazon, Joshua R; Djokhdem, Abdul H; van den Heuvel, Eleanor A; Wittich, Walter; Jutai, Jeffrey W
The goal of this narrative review is to evaluate the efficacy of available questionnaires for assessing the outcomes of "continence difficulty" interventions and to assess the selected questionnaires concerning aspects of stigmatization. The literature was searched for research related to urinary incontinence, as well as questionnaires and rating scale outcome measurement tools. The following sources were searched: Cochrane Library, EMBASE, Medline, and PubMed. The following keywords were used separately or in combination: "Urinary incontinence, " "therapy, " "treatment outcome, " "patient satisfaction, " "quality of life, " "systematic reviews, " "aged 65+ years, " and "questionnaire." The search yielded 194 references, of which 11 questionnaires fit the inclusion criteria; 6 of the 11 questionnaires did not have any stigma content and the content regarding stigma that was identified in the other five was very limited. A representative model of how stigma impacts continence difficulty interventions was proposed. While the 11 incontinence specific measurement tools that were assessed were well researched and designed specifically to measure the outcomes of incontinence interventions, they have not been used consistently or extensively and none of the measures thoroughly assess stigma. Further studies are required to examine how the stigma associated with continence difficulty impacts upon health care interventions.